Physician’s autonomy in the face of AI support: walking the ethical tightrope - Funer, Florian; Wiesing, Urban (Frontiers in Medicine, 2024)
The introduction of AI support tools raises questions about the normative orientation of medical practice and the need to rethink its basic concepts. One of these concepts that is central to the discussion is the physician's autonomy and its appropriateness in the face of high-powered AI applications. In this essay, a differentiation of the physician's autonomy is made on the basis of a conceptual analysis. It is argued that the physician's decision-making autonomy is a purposeful autonomy. The physician's decision-making autonomy is fundamentally anchored in the medical ethos for the purpose to promote the patient's health and well-being and to prevent him or her from harm. It follows from this purposefulness that the physician's autonomy is not to be protected for its own sake, but only insofar as it serves this end better than alternative means. We argue that today, given existing limitations of AI support tools, physicians still need physician's decision-making autonomy. For the possibility of physicians to exercise this decision-making autonomy in the face of AI support, we elaborate three conditions: 1.) sufficient information about AI support and its statements, 2.) sufficient competencies to integrate AI statements into clinical decision-making, and 3.) a context of voluntariness that allows, in justified cases, deviations from AI support. If the physician should fulfil his or her moral obligation to promote the health and well-being of the patient, then the use of AI should be designed in such a way that it promotes or at least maintains the physician's decision-making autonomy.